Professional formation and the final thesis in European teacher education: a fusion of academic and professional orientation. Issue 3 (3rd July 2019) - Råde, Anders
ABSTRACT: This paper deals with possibilities and difficulties involved in the integration of academic and professional goals in two final thesis models in European teacher education, the thesis model and the portfolio model. The methodology used is a review of relevant research articles. The thesis model was identified in 19 articles and the portfolio model in 41 articles. Five dimensions were found to promote the integration of the two kinds of goals while four hamper this integration. The dimensions identified are similar in the two models. The implications of this result for future teachers are discussed using the concepts of vertical and horizontal discourses. One such implication is that teacher education should use the adaptive function of the final thesis in a more developed way in order to strengthen the fusion of academic and professional orientation in the education.